Ḥayāt-i Maulānā Aḥmad Ra̤zā Ḵẖān Barelvī . - Masʻūd Aḥmad, Muḥammad, 1930- (Islāmī Kutub Ḵẖānah ; Milne kā patā, Naẕirsanz Pablisharz, 1981)
Biography of Aḥmad Ra̤zā Ḵẖān, 1856-1921, founder of the Bareilly School of Islamic theology.